Implementasi Metode CPM dan PERT Pada Proyek Perangkat Lunak Sistem Administrasi Manajemen Pengujian Akhir Semester Kasus ID Core Indonesia: Perencanaan, CPM, PERT - Raden Imam Babus Salam (Jurnal Repositor, 2023)
Planning activities in a project is a very important part because the planning is fundamental so that the project can run smoothly and the project can be carried out according to the specified time. The success or failure of planning a project can occur due to lack of planning and less effective control. As a result, the project is not efficient. In addition, it can cause delays, decrease the quality of work and increase implementation costs. In the project schedule planning step, the Project manager will determine the sequence of work activities carried out during the project, the work sequence and duration of the activities on the project are adjusted to the type of software project being carried out, so that the sequence of work activities and duration of work can be adjusted to the client's needs. In a company, good management is needed so that it can create structured work. PERT (Program Evaluation and Review Technique) and CPM (Critical Path Method) are mechanisms used to organize and sequence activities in companies that are complex and interdependent. This method has the advantage of analyzing projects in terms of estimating the project completion time by finding the critical path, identifying the start and end time of each activity to find the project schedule, and calculating the amount of slack time for each activity so as to minimize project delays. ID Core Indonesia is a company that was founded on October 20, 2018. A new digital startup in Malang city that focuses on software development services (project base). ID Core Indonesia focuses on developing information systems based on website technology and mobile apps. Based on the implementation of the CPM and PERT methods on the management system administration software project, the end-of-semester test of the ID Core Indonesia case shows the project completion within a period of 40 days with a probability of 82%.